IMPLEMENTATION OF PANCASILA STUDENT PROFILE (P3) THROUGH HIZBUL WATHAN EXTRACURRICULAR - Fardiansyah, Yuke; Ikhwan, Afiful; Sumaryanti, Lilis (STKIP Pesisir Selatan, 2025)
The purpose of this study is to examine application of the Pancasila Student Profile through extracurricular activities of Hizbul Wahan at Muhammadiyah 1 Senior High School, Ponorogo. The Pancasila student profile acts as the main reference that directs educational policies including being a reference for educators in building the character and competence of students. The Pancasila student profile must be understood by all stakeholders because it is considered important. Muhammadiyah 1 Senior High School, Ponorogo is one of the private schools that has implemented the Independent Curriculum, one of which is the Pancasila Student Profile (P3) dimension. Hizbul Wathan is one of the scouts in Indonesia that is related to outdoor learning activities. The research method used is qualitative research with a field approach. Data collection was carried out through observation, interviews, and documentation. The results of the study show that 1) Muhammadiyah Senior High School 1 Ponorogo has implemented part of the Independent Curriculum, namely the Pancasila Student Profile (P3), one of which is through the Hizbul Wathan extracurricular, 2) The dimensions of the Pancasila Student Profile (P3) that have been applied in extracurricular activities are faith, devotion to God Almighty; independent; mutual cooperation; and creative. This study concludes that the Hizbul Wathan extracurricular activity is an effective forum for implementing the Pancasila Student Profile at Muhammadiyah Senior High School 1 Ponorogo.